IMPLEMENTASI MANAJEMEN PEMBELAJARAN TAHFIDZUL QURAN DI MI MUHAMMADIYAH KARANGWUNI POLOKARTO - Indah Nurhidayati (MAMBA'UL 'ULUM, 2022)
The results of the study show that: (1) Tahfidzul Quran learning planning is done through the preparation of memorization targets and the determination of effective weeks and days in each semester; (2) Organizing is carried out through the division of tasks and responsibilities as well as the construction of the structure of the tutoring teacher; (3) The mobilization is carried out through the coordination meeting of the Tahfidz coordinator as a shering forum for decision making and direction of the Tahfidzul Quran learning program and the implementation of learning is carried out every Monday-Friday; and (4) Supervision is carried out through assessing teacher performance at the end of December and June. The highest achievement target for the second year of the implementation of the Tahfidzul Quran's 2017/2018 year program is juz 29 and 30, the lowest target for class 1 is juz 30 to Surat al Ghasyiyyah. For class 1, 85% of the target is achieved and 11% of students exceed the target. Class 2 targets reached 19%. Class 3, 10.86% reached the target and 035% of students exceeded the target. Class 4 tarjet reached 12.44%. Class 5 targets reached 4.24%, and the last grade 6 target reached 13.79% and 1.5% of students exceeded the target.